Student’s thinking to identify concave plane based on Gregorc model - Surya Enjang Krisdiantoro; Erlina Prihatnani (Beta: Jurnal Tadris Matematika, 2019)
[English]: Mathematics learning should facilitate students' construction of knowledge. In constructing mathematics knowledge, students involve various types of thinking processes and styles. This qualitative research aimed to describe the process of students’ thinking in identifying concave plane based on Gregorc’s model of thinking style. It involved thirty-three 9th-grade students with a different style of thinking. Data were collected through tests, questionnaire, and non-structured interview then descriptively analyzed to reveal students’ thinking process and styles. The present study found two different thinking styles, namely Sequential Concrete and Random Abstract from students who successfully identified the concave plane as a kite. There were different thinking processes in the development of definition, opinion, and conclusions from subjects with different thinking styles. However, the difference in the thinking process from each thinking styles do not hamper students’ success in constructing knowledge. Keywords: Thinking process, Concave place, Thinking style, Gregorc model [Bahasa]: Pembelajaran matematika seharusnya memfasilitasi siswa membangun pengetahuan sendiri. Dalam membangun pengetahuan, siswa melibatkan beragam proses dan gaya berpikir. Penelitian kualitatif ini bertujuan untuk mendeskripsikan proses berpikir siswa dalam mengidentifikasi bangun datar concave berdasarkan gaya berpikir model Gregorc. Subjek penelitian adalah 33 siswa kelas IX SMP yang memiliki gaya berpikir berbeda. Data dikumpulkan melalui tes, angket, dan wawancara non-terstruktur kemudian dianalisis secara deskriptif untuk mengungkap gaya dan proses berpikir siswa. Penelitian ini menemukan dua gaya berpikir berbeda yaitu Sekuensial Konkret dan Acak Abstrak dari siswa yang berhasil mengidentifikasi bangun datar concave sebagai layang-layang. Terdapat perbedaan proses berpikir dalam pembentukan pengertian, pembentukan pendapat, dan penarikan kesimpulan dari siswa dengan gaya berpikir berbeda. Namun demikian, perbedaan gaya berpikir dari setiap proses berpikir tidak membatasi keberhasilan siswa dalam mengkonstruksi suatu pengetahuan. Kata kunci: Proses berpikir, Gaya berpikir, Bangun concave, Model Gregorc